2015
DOI: 10.1186/1471-2105-16-s10-s5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and categorization of bacteria habitats using shallow linguistic analysis

Abstract: BackgroundInformation regarding bacteria biotopes is important for several research areas including health sciences, microbiology, and food processing and preservation. One of the challenges for scientists in these domains is the huge amount of information buried in the text of electronic resources. Developing methods to automatically extract bacteria habitat relations from the text of these electronic resources is crucial for facilitating research in these areas.MethodsWe introduce a linguistically motivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, in the COPIOUS project, to support the conservation of the Philippine biodiversity, our initial emphasis is on organisms that are highly endangered with extinction, such as birds, fish, mammals and plants; microorganisms will be dealt with in future work. As a result, the types of taxon names and habitats annotated in Bacteria Biotope and recognised by tools trained on the corpus (Björne and Salakoski 2015, Karadeniz and Özgür 2015, Lavergne et al 2015) are not suitable for supporting our immediate aims. While Bacteria Biotope concerns the biomedical domain, the other corpora mentioned above, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the COPIOUS project, to support the conservation of the Philippine biodiversity, our initial emphasis is on organisms that are highly endangered with extinction, such as birds, fish, mammals and plants; microorganisms will be dealt with in future work. As a result, the types of taxon names and habitats annotated in Bacteria Biotope and recognised by tools trained on the corpus (Björne and Salakoski 2015, Karadeniz and Özgür 2015, Lavergne et al 2015) are not suitable for supporting our immediate aims. While Bacteria Biotope concerns the biomedical domain, the other corpora mentioned above, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Features were also extended between mentions and antecedents. Recognizing the importance of coreference features, several systems [181][182][183][184] subsequently implemented coreference resolution across sentences. They showed that to facilitate extracting specific types of relations, heuristic/rule-based coreference resolution tends to outperform domain-adapted statistical machine learning systems.…”
Section: Integrating Coreference Resolutionmentioning
confidence: 99%
“…Bannour et al (2013) combined automatically learned rules from training set via machine learning and the rules constructed on the basis of the OntoBiotope ontology to identify bacteria and habitat entities (Nédellec, 2015). Karadeniz and Özgür (2015) designed recognition rules based on multiple shallow syntactic analysis such as sentence segmentation, part-of-speech tagging, partial parsing, and lemmatization. Rule-based methods relies heavily on domain thesauri.…”
Section: Bacteria Biotope Ner Taskmentioning
confidence: 99%